2001
DOI: 10.1006/jmaa.2001.7610
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Composition Operators on Hardy Spaces

Abstract: Ž .Let , be analytic functions defined on ‫,ބ‬ such that ‫ބ‬ : ‫.ބ‬ The operator Ž . given by f ¬ f ( is called a weighted composition operator. In this paper we deal with the boundedness, compactness, weak compactness, and complete continu-Ž . ity of weighted composition operators on Hardy spaces H 1 F p -ϱ . In p particular, we prove that such an operator is compact on H if and only if it is 1 weakly compact on this space. This result depends on a technique which passes the weak compactness from an operator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 7 publications
0
49
0
1
Order By: Relevance
“…In [7] it was further shown that every weakly compact W ψ,ϕ on H 1 is compact. Moreover, because A 1 is isomorphic to ℓ 1 , it has the Schur property, and so every weakly compact linear operator on A 1 is compact; see [19, p. 302].…”
Section: Weighted Composition Operators On General Vector-valued Funcmentioning
confidence: 99%
See 1 more Smart Citation
“…In [7] it was further shown that every weakly compact W ψ,ϕ on H 1 is compact. Moreover, because A 1 is isomorphic to ℓ 1 , it has the Schur property, and so every weakly compact linear operator on A 1 is compact; see [19, p. 302].…”
Section: Weighted Composition Operators On General Vector-valued Funcmentioning
confidence: 99%
“…Compactness and weak compactness of W ψ,ϕ are well understood on H 1 and A 1 : Function-theoretic characterizations exist for the compactness of W ψ,ϕ on both H 1 and A 1 [7,9]. In [7] it was further shown that every weakly compact W ψ,ϕ on H 1 is compact.…”
Section: Weighted Composition Operators On General Vector-valued Funcmentioning
confidence: 99%
“…However, this is not a necessary and sufficient condition for boundedness, although clearly we require h ∈ H 2 (D) (see [9] for more details). Weighted composition operators on Hardy and Bergman spaces have been much studied in recent years (see, for example, the articles [1,2,3,4,6,9,11] and the survey [16]). In particular, their boundedness on H 2 (D) is characterised in [3,6,11], as is explained further in Section 2.…”
Section: Introductionmentioning
confidence: 99%
“…We also obtain estimates for the essential norm of weighted composition operators on these spaces. For weighted composition operators on spaces of holomorphic functions one can refer to [2,4,11,17,20,23] and the references therein.…”
Section: Introductionmentioning
confidence: 99%